2013
DOI: 10.3378/027.085.0307
|View full text |Cite
|
Sign up to set email alerts
|

The Andaman Islanders in a Regional Genetic Context: Reexamining the Evidence for an Early Peopling of the Archipelago from South Asia

Abstract: The indigenous inhabitants of the Andaman Islands were considered by many early anthropologists to be pristine examples of a "negrito" substrate of humanity that existed throughout Southeast Asia. Despite over 150 years of research and study, questions over the extent of shared ancestry between Andaman Islanders and other small-bodied, gracile, dark-skinned populations throughout the region are still unresolved. This shared phenotype could be a product of shared history, evolutionary convergence, or a mixture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…We have shown that Andamanese and Japanese individuals carrying haplogroup D separated around ~ 53 kya, coinciding with most of the other major OOA haplogroup divergences. We have also demonstrated, using autosomal data, that the Andamanese are indeed an out-group to East Asian populations, which was also shown before (Chaubey and Endicott 2013;Aghakhanian et al 2015).This strongly suggests that haplogroup D does not indicate a separate ancestry for Andamanese populations. Rather, haplogroup D was part of the standing variation carried by the OOA expansion, and later lost from most of the populations except in Andaman and partially in Japan and Tibet.…”
Section: Discussionsupporting
confidence: 56%
“…We have shown that Andamanese and Japanese individuals carrying haplogroup D separated around ~ 53 kya, coinciding with most of the other major OOA haplogroup divergences. We have also demonstrated, using autosomal data, that the Andamanese are indeed an out-group to East Asian populations, which was also shown before (Chaubey and Endicott 2013;Aghakhanian et al 2015).This strongly suggests that haplogroup D does not indicate a separate ancestry for Andamanese populations. Rather, haplogroup D was part of the standing variation carried by the OOA expansion, and later lost from most of the populations except in Andaman and partially in Japan and Tibet.…”
Section: Discussionsupporting
confidence: 56%
“…S2A). This bottleneck ~20k ybp roughly coincides with the deglaciation following the last glacial maximum and may point towards local migration and/or isolation (13,14). In case of the Austroasiatic speaking HG tribes from mainland SAS, in concordance with the islanders, we observed a pronounced bottleneck ~10k ybp, but unlike the islanders, we did not observe a population bottleneck ~20k ybp (Fig.…”
Section: Fig 2 Comparison Of Hg and Non-hg Demography Asupporting
confidence: 66%
“…Actually, the southern component is the most prevalent population in Andaman. Of particular interest is the fact that when populations of southeast Asia and Near Oceania were incorporated to these broad genome analyses, the Andaman Islanders showed a closer affinity with southeast rather than South Asian populations [117, 118]. It is evident that our mtDNA interpretation and the autosomal results give a very similar picture.…”
Section: Resultsmentioning
confidence: 67%